WIDYA (Web Information Dialog Your Assistant): AI-Powered Chatbot for Library Online Service Innovation - Ayu Pratiwi, Melati; Syahbaniar, Desy; Hanif Robbani, Azzam (Forum Perpustakaan Perguruan Tinggi Indonesia, 2023)
The library is a source of information literacy, so it requires adequate facilities and infrastructure to support this. To get satisfaction from the academic community, it is necessary to improve more practical information systems and make it easier for officers and visitors. This research develops a Chatbot application used as a library online customer service at the Widya Cipta Husada Malang Institute of Health Technology to convey library information. This research uses a qualitative method. System development uses the stages of the waterfall programming method. Stages consist of requirements analysis, system design, implementation, and testing. They are using vscode software as an editor and phyton, HTML, and JavaScript programming languages. The Chatbot system uses AIML (Artificial Intelligence Markup Language) as a knowledge base. The Chatbot system can answer and have conversations with users according to knowledge related to library information. The expected results of the system can help visitors and librarians in delivering fast and accurate information. The results of this study show that the WIDYA Chatbot system can run well and accurately because it has an accuracy of 90%.